The widespread proliferation of anglicisms on digital media platforms - Petrosyants , Ernst (The Lingua Spectrum, 2025)
This article examines the use of anglicisms in Russian‑language online media, emphasizing their role in reflecting social, political, and cultural transformations. It analyzes terms such as hypercar, Batmobile, Popemobile, Trumpmobile (гиперкар, бэтмобиль, папамобиль, трампомобиль), as well as words with the suffix ‑ing (фишинг, имиджинг, имиджмейкинг), exploring their English origin, borrowing mechanisms, and adaptation in Russian, along with occasionalisms formed with ‑ing (e.g., зацепинг). Through linguistic analysis and examples drawn from media texts, the study demonstrates how these neologisms enrich the Russian lexicon by providing precise terminology for emerging concepts – particularly in the automotive industry and beyond. It highlights the chronology of the neologisms image‑maker (имиджмейкер) and image‑making (имиджмейкинг), and clarifies the meaning of imaging (имиджинг) as a term for visualization. These terms are formed through direct borrowing, partial calquing, or blending, reflecting the influence of the English language and globalization. Online media platforms play a key role in popularizing these words by featuring them in news reports, articles, and social networks, thereby accelerating their integration into the language. This research contributes to understanding linguistic processes in the digital communication era, emphasizing the balance between innovation and the preservation of normative language standards.